Determinants of Micro and Small Business Resilience in Indonesia - Adhi, Antono Herry Purnomo; Hartiningsih, Tri (Universitas Dian Nuswantoro Semarang, 2024)
This study aims to identify the factors that determine the resilience of Micro and Small Enterprises in Indonesia between 2012 and 2021. Estimates use the Ordinary Least Square (OLS) method for the variables of economic growth, credit business, and perceptions of corruption to estimate the effect of resilience on MSEs. The estimation results show that the variable economic growth has an effect on the resilience of MSEs, while the variables business credit and perceptions of corruption have no effect. Keywords:MSE resilienceeconomic growthbusiness creditcorruption